Hasil Belajar Peserta Didik Melalui Model Pembelajaran Nodar (Numbering, Observing, Discussing, Answering, Repetition) - Syam Suriani Aris; Andi Maulana; Zulkarnaim (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2022)
NODAR learning model makes students actively discuss and observe which increases motivation and learning outcomes. This study is a pseudo-experiment with a non-equivalent pretest posttest control group research design. The purpose of the study was to determine the influence of the application of the NODAR learning model on learning outcomes of students. The study population was all students of class XI of SMAN 3 Enrekang as many as 206 students with a sample of 35 in the experimental class and 32 in the control class. Research instruments are in the form of motivational questionnaires and tests. Data analysis techniques use statistics and inferential statistics with t-tests. The results showed that the learning motivation of students of class XI MIPA in the experimental class obtained an average score of 102.42 while those in the control class were 98. Meanwhile, the learning outcomes in the experimental class obtained an average score of 76.85 while in the control class a score of 70 was obtained. The results of the inferential analysis of learning motivation obtained a sign value of 0.034 and for learning outcomes a sign value of 0.000 was obtained which showed that the sign < α = 0.00 < 0.05. Based on the results of the analysis, it was concluded that there was an influence of the application of the NODAR learning model on the motivation and learning outcomes of class XI students on the immunity system material at SMAN 3 Enrekang.